Power Control Study of Hydrokinetic Power Plants in presence of Wake Effect - Muhammad Ikhsan; Muhammad Rizal Fachri (PTE FTK UIN Ar-Raniry, 2023)
Hydrokinetic power plants are able to produce energy only by harnessing the kinetic energy of flowing water. Compared to dam-based hydroelectric power plants, hydrokinetic power plants have minimal impact on several issues e.g. environmental, health, social and political conflict. Similar to wind turbines in a wind farms, hydrokinetic turbines in tidal farms also generate a wake effect, which results in less kinetic energy on downstream turbines compared to upstream turbines. This article shows the simulation results of three hydrokinetic power generation systems installed in series on the same water stream such as river or aqueduct. The upstream turbine generates wake effect and resulting a velocity deficit both in the two downstream turbines. Bastankhah Porté-Agel model for wake effect was used in this study. The simulation results show that the downstream turbine cannot maintain the given voltage reference and loses the stability of the power control if the water velocity decreases. Several recommendations regarding series configuration of the hydrokinetic system are also presented in order to support the control stability.